The "Black Experience" as Preparation for Participation in Global Partnerships - Talley, Cynthia (The Asbury journal, 2022)
The lived experiences of African Americans, along with their reliance on God, serve as preparation for participation in global mission partnerships. The "Black Experience," characterized by suffering, dehumanization, violence, and survival has provided the African American community with a toolkit that can be used to teach others how to survive their own suffering as they too rely on God. Long-term African American missionaries have sent out a clarion call requesting that the African American church step up to the plate and join them in spreading the Gospel message "in Jerusalem, and in all Judea and Samaria, and to the ends of the earth" (Acts 1:8).